2010
DOI: 10.1373/clinchem.2010.152264
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Quantification of Apolipoprotein A-I and Apolipoprotein B by Liquid-Chromatography–Multiple- Reaction–Monitoring Mass Spectrometry

Abstract: BACKGROUND If liquid-chromatography–multiple-reaction–monitoring mass spectrometry (LC-MRM/MS) could be used in the large-scale preclinical verification of putative biomarkers, it would obviate the need for the development of expensive immunoassays. In addition, the translation of novel biomarkers to clinical use would be accelerated if the assays used in preclinical studies were the same as those used in the clinical laboratory. To validate this approach, we developed a multiplexed assay for the quantificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
123
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 33 publications
7
123
1
1
Order By: Relevance
“…In at least one study, quantification of clinically useful biomarker proteins in plasma by multiplexed LC-MRM/MS has demonstrated promise in the absolute quantification of biomarkers in plasma [15 ]. Using external calibration and comparison with existing clinical immunoassays for ApoA-I and ApoB, the authors confirmed that the direct analysis of tryptic digests is a viable approach, and may someday offer a cost-efficient and sample-saving analysis method for the clinical laboratory.…”
Section: Enzymatic Digestionmentioning
confidence: 95%
“…In at least one study, quantification of clinically useful biomarker proteins in plasma by multiplexed LC-MRM/MS has demonstrated promise in the absolute quantification of biomarkers in plasma [15 ]. Using external calibration and comparison with existing clinical immunoassays for ApoA-I and ApoB, the authors confirmed that the direct analysis of tryptic digests is a viable approach, and may someday offer a cost-efficient and sample-saving analysis method for the clinical laboratory.…”
Section: Enzymatic Digestionmentioning
confidence: 95%
“…Apolipoprotein quantification by liquid chromatography ID/MS (LC-ID/MS) was first reported in the late 1990s by Barr et al for apoA-I [58] and was further applied to other apolipoproteins (apoB, C and E) in the following years [59][60][61].…”
Section: Apolipoprotein Profiling By Liquid Chromatography Isotopic-dmentioning
confidence: 99%
“…After digestion, apolipoprotein-specific tryptic peptides were identified for each major class of apolipoproteins, and some of them were selected for quantification by ID/MS [60][61][62]. ID/MS quantification uses synthetic labeled entities with 13 C, 15 N or deuterium as internal standards (IS) to spike the samples.…”
Section: Apolipoprotein Profiling By Liquid Chromatography Isotopic-dmentioning
confidence: 99%
See 2 more Smart Citations